2014
DOI: 10.1088/0004-637x/792/1/45
|View full text |Cite
|
Sign up to set email alerts
|

Optical Spectroscopy and Velocity Dispersions of Galaxy Clusters From the SPT-Sz Survey

Abstract: We present optical spectroscopy of galaxies in clusters detected through the Sunyaev-Zel'dovich (SZ) effect with the South Pole Telescope (SPT). We report our own measurements of 61 spectroscopic cluster redshifts, and 48 velocity dispersions each calculated with more than 15 member galaxies. This catalog also includes 19 dispersions of SPT-observed clusters previously reported in the literature. The majority of the clusters in this paper are SPT-discovered; of these, most have been previously reported in othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(152 citation statements)
references
References 52 publications
7
144
0
1
Order By: Relevance
“…These spectra were initially obtained as part of a spectroscopic redshift campaign that targeted, primarily, red sequence galaxies. The full details of this spectroscopic follow-up are provided in Ruel et al (2014) and Bleem et al (2015). For each spectrum, we measure the [O II] and Hδ equivalent widths and the 4000 Å break strength (D 4000 ), via indices defined by Balogh et al (1999).…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…These spectra were initially obtained as part of a spectroscopic redshift campaign that targeted, primarily, red sequence galaxies. The full details of this spectroscopic follow-up are provided in Ruel et al (2014) and Bleem et al (2015). For each spectrum, we measure the [O II] and Hδ equivalent widths and the 4000 Å break strength (D 4000 ), via indices defined by Balogh et al (1999).…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…We refer to Beers et al (1990) for details in their computation and the algorithm 4 used for these calculations. We refer the reader to Ruel et al (2014) for a discussion of measurements of velocity dispersions in the regime of low number of spectroscopic members, in the context of galaxy clusters selected by SunyaevZeldovich effect in the South Pole Telescope data. Both estimators are computed for each cluster, although it is clear that a high enough number of members must enter the derivation to ensure robust measurements.…”
Section: Radial Velocity Dispersionsmentioning
confidence: 99%
“…For each cluster, high signal-to-noise spectra for ∼200 cluster members were acquired with MMT (Multi Mirror Telescope)/Hectospec. Ruel et al (2014) presented optical spectroscopy of galaxies in clusters detected through the SZ effect with the South Pole Telescope (SPT). They reported measurements of 61 spectroscopic cluster redshifts, and 48 velocity dispersions each calculated with more than 15 member galaxies.…”
Section: Source Catalogsmentioning
confidence: 99%
“…To standardise the uncertainties, we followed Ruel et al (2014). They found that the uncertainty in the velocity dispersion σv is well described by…”
Section: Merged Catalogmentioning
confidence: 99%
See 1 more Smart Citation